UPAYA MENINGKATKAN PERCAYA DIRI ANAK USIA 4-5 TAHUN DENGAN METODE MENGGAMBAR BEBAS DI RA HIDAYAT KOTA PROBOLINGGO: THE EFFORTS TO INCREASE SELF-CONFIDENCE OF CHILDREN AGED 4-5 YEARS WITH FREE DRAWING METHOD IN RA HIDAYAT PROBOLINGGO - Siti Agustini Setia Ningsih; Aries Dirgayunita (Program Studi PG-PAUD Universitas PGRI Adi Buana Surabaya, 2023)
This study aims to increase the self-confidence of children aged 4-5 years by drawing freely at RA HIDAYAT for the 2022/2023 Academic Year. The subjects of this study were 12 children in group A. The type of this research was Classroom Action Research (PTK) which was carried out in two cycles where each cycle consisted of four stages, namely action planning, action implementation, evaluation/observation and reflection. Collecting data in this study using observation sheets. Based on the results of improving learning in cycle I to cycle II, where children who were confident at the beginning of the study were 8%, after the action was carried out cycle I showed an increase in children's self-confidence by 42% and finally, the results of implementing cycle II action showed an increase in confidence self in children by 83%. In the results of cycle I and cycle II there was an increase, so using free drawing to increase self-confidence in children was effectively implemented in RA Hidayat, Probolinggo city.